2015
DOI: 10.1007/s13369-015-1731-9
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy System Methodology for Concrete Mixture Design Considering Maximum Packing Density and Minimum Cement Content

Abstract: Concrete mix proportioning could be referred to the process of determining the quantities of concrete ingredients using local materials to achieve specific characteristics of the concrete. Among the most important parameters affecting the performance of concrete are the packing density and the grading curve of the aggregates. Better packing of aggregates improves the strength, durability, elastic modulus and creep of the concrete. Accordingly, by increasing packing density and decreasing cement content, enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They concluded that the ANFIS model performs equally well or even superior to the FES model, even though it requires much less effort or subject expertise than that needed in the FES model, in which the if-else rules have to be manually input into the system by an expert. Ghoddousi et al [13] presented a set of FES and ANFIS submodels for the mix design of concrete. It was concluded that the model successfully provides the quantities of the various components for the mix design, ensuring maximum packing density and minimum cement content for a given design strength.…”
Section: Anfis Modeling In Concrete Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the ANFIS model performs equally well or even superior to the FES model, even though it requires much less effort or subject expertise than that needed in the FES model, in which the if-else rules have to be manually input into the system by an expert. Ghoddousi et al [13] presented a set of FES and ANFIS submodels for the mix design of concrete. It was concluded that the model successfully provides the quantities of the various components for the mix design, ensuring maximum packing density and minimum cement content for a given design strength.…”
Section: Anfis Modeling In Concrete Technologymentioning
confidence: 99%
“…There are numerous applications of the ANFIS in the fields of concrete technology and structural engineering. The ANFIS has been used to model concrete strength in numerous studies [12][13][14]. In addition, the ANFIS is used for the prediction of concrete compressive strength based on various nondestructive tests [15][16][17].…”
Section: Prediction Of Compressive Strength Using An-fis Model 21 Application Of Anfis Model To Concretementioning
confidence: 99%